Analysis of the Perceptions of Primary Care Physicians in Spain Regarding the Relationship Between Health and wine. - José Clemente-Ricolfe; Dolores Miralles-Enrique (Wine Business Journal)
This study aims to determine the attitudes of primary care physicians in Spain towards the consumption of wine and its effects on health. To this end, 199 surveys were conducted on primary care physicians in Spain. The study concludes that medical professionals associate moderate wine drinking with possible cardiovascular benefits, although there are three groups of physicians with different attitudes toward the consumption of wine and its relationship to health. All of the groups, however, coincide in the view that the amount of wine consumed must be limited. This paper makes an important contribution to research knowledge as it focuses on perceptions of the wine-health relationship among primary care physicians in particular.